Forests, policies and people on the Central American agricultural frontier - Kaimowitz, D.; Paupitz, J. (1999)
Forests cover between 17 and 19 million ha of the Central American isthmus. Most of this is broadleaved forest on the Atlantic side of the isthmus. The size and contribution of these forests vary greatly between the Central American countries, from Belize, with over 80% of its land in forests, to El Salvador, where little forest remains. The forests' main contribution to society comes from local uses and the environmental services they provide. Forest products, per se, contribute less to the region's economies but play key roles in the livelihood strategies of many poor families. Over the last 50 years, forest cover has declined rapidly in the region, caused mostly by the expansion of crops and livestock. This article traces the evolution of the agricultural frontier in Central America prior to and during the political-military conflict that engulfed the region until 1990. Then it looks at more recent changes in policies and forest cover, and concludes with recommendations regarding future management of frontier areas and forests. Although there is occasional reference to Belize and El Salvador, focus is mostly on Costa Rica, Guatemala, Honduras, Nicaragua and Panama.